Differential systems with algebraic and non-algebraic limit cycles explicitly given - Boukoucha, R. (Methods of Functional Analysis and Topology, 2022)
In this paper we give an explicit expression of invariant algebraic curves of a multi-parameter planar polynomial differential systems, then we prove that these systems are integrable and we introduce an explicit expression of a first integral. Moreover, we determine sufficient conditions for these systems to possess two limit cycles: one of them is algebraic and the other one, explicitly given, is shown to be non-algebraic. Concrete examples exhibiting the applicability of our results are introduced. Надано явний вираз інваріантних алгебраічних кривих багатопараметричної поліноміальної диференціальної системи на площині. Доводено, що ці системи є інтегровні, і наведено явний вираз дляй першого інтеграла. Більш того, отримано достатні умови для того, щоб ці системи мали два граничні цикли: один з яких є алгебраїчний, і доведено, що інший цикл, для якого отримано явний вираз, не є алгебраічний. Надано конкретні приклади, які демонструють можливість застосування отриманих результатів.